Magnitude and Predictors of Medication Administration Errors Among Nurses in Public Hospitals in Northeastern Ethiopia - Dagne Belete Gebrye MSc; Muluken Amare Wudu MSc; Molla Kassa Hailu MSc (SAGE Publishing, 2023)
Introduction Currently, patient safety and quality of care have become a public health concern. However, medication administration errors are common in global medical settings and may cause problems ranging from the subtle to the fatal. Objective To assess the Magnitude and determinant factors of Medication Administration Errors among nurses working in the public hospitals in the Eastern Amhara region, Northeastern Ethiopia, 2022. Methods A multicenter hospital-based cross-sectional study design was used in South Wollo Zone public hospitals from February-March 2022, with 423 nurses selected using a simple random method. Data were collected using a pretested questionnaire, entered, and analyzed using EpiData 4.6.0 and SPSS 26. Predictors of medication administration errors were identified by multivariate logistic regression. Result Magnitude of Medication Administration Errors in the study areas was 229 (55%), 95% CI [0.501, 0.599]. Service provision to ≥ 11 patients per day (AOR: 2.52, 95% CI [1.187, 6.78]), interruption (AOR: 4.943, 95% CI [2.088, 11.712]), lack of training (AOR: 6.35, 95% CI [3.340, 7.053]), ≥ 4 years and 5-9 years of experience respectively (AOR: 3.802, 95% CI [1.343, 10.763]), (AOR: 2.804, 95% CI [1.062, 7.424]) were factors associated with Medication Error. likewise, shortage of time (AOR: 5.637, 95% CI [2.575, 12.337]), lack of guidelines (AOR: 2.418, 95% CI [1.556, 5.086]), workload (AOR: 7.32, 95% CI [3.146, 17.032]) and stress (AOR: 12.061, 95% CI [33.624, 53.737]) were determinant factors for Medication Administration Errors. Conclusion and recommendation In the current study, medication administration errors were common. Patient load, interruption, nurse's service experience, time deficit, stress, a lack of training, and the absence of guidelines were associated with medication administration errors. Therefore, ongoing training, the availability of guidelines, the presence of a good working environment, and the retention of experienced nurses can all be critical steps in improving patient safety.